PENGARUH PEMBERIAN KOMPOS JERAMI PADI TERHADAP PERTUMBUHAN BIBIT KARET (Hevea brasiliensis Muell Arg.) - Putri, Wike Widya; Nurhidayah, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The research aims to study the effect and to obtain the best dose of rice straw compost on the growth of rubber seedling. The experiment has been conducted at the experimental farm of the Faculty of Agriculture University of Riau, Pekanbaru from Mei to September 2018. The experimental unit was arranged in a completely randomized design (RAL), consisting of 6 treatments and 3 replications. The treatment consisted of the rice straw compost, a.i : 0, 40, 120, 160 and 200 g/seedling. Parameter observed were plant height increment, increase of stem diameter, number of leaves increament, the width of the leaves strands and the long increase in the leaves strands. Data were analyzed statistically using analysis comparent by using Duncan New Multiple Range Test dose of 5 %. The results showed that the plant height increment, increase of stem diameter, number of leaves increament,the width of the leaves strands and the long increase in the leaves strands. The dose of rice straw compost at 200 g/seedling produced the best growth of rubber seedling.Keyword :Hevea brasilliensis Muell Arg., rice straw compost